Girl rising : changing the world one girl at a time - Stone, Tanya Lee (Ember, 2019)
Examines the Girl Rising campaign that helps girls around the world receive an education and avoid poverty, child marriage, slavery, and sex trafficking. Features the true success stories of nine girls in the film of the same name as well as over twenty-five others. Features color photographs, infographics, and resources.